An update on diagnosis and therapy of metabolic myopathies. (2nd December 2018) - Finsterer, Josef
ABSTRACT: Introduction : Metabolic myopathies are a heterogeneous group of disorders characterized by inherited defects of enzymatic pathways involved in muscle fiber energetics. Diagnosing metabolic myopathies requires a thoroughly taken individual and family history, a meticulous neurologic exam, exercise tests, blood and urine tests, needle-electromyography, nerve-conduction studies, muscle biopsy, targeted genetic tests, or next-generation sequencing. There is limited evidence from the literature to guide treatment of metabolic myopathies. Treatment is largely limited to non-invasive/invasive symptomatic measures. However, promising results have been achieved with enzyme replacement therapy in Pompe disease (GSD-II). Primary coenzyme-Q deficiency responds favorably to coenzyme-Q supplementation. MNGIE responds to allogeneic hematopoietic stem cell transplantation, orthotopic liver transplantation, and carrier erythrocyte entrapped thymidine phosphorylase enzyme therapy. MADD may respond to riboflavin. Areas covered : This review aims to summarize and discuss recent findings and new insights concerning diagnosis and treatment of metabolic myopathies. Expert commentary : Except for GSD-II, coenzyme-Q deficiency, and MNGIE, treatment of metabolic myopathies is usually palliative and supportive (non-invasive or invasive). Non-invasive symptomatic treatment includes physiotherapy, diet, administration of drugs, conservative orthopedic measures, and respiratory non-invasive support. Important is the avoidance of triggers for episodic forms of fatty acid oxidation disorders. Invasive measures include orthopedic surgery and invasive mechanical ventilation.